2018
DOI: 10.3389/fpls.2018.00410
|View full text |Cite
|
Sign up to set email alerts
|

FdC1 and Leaf-Type Ferredoxins Channel Electrons From Photosystem I to Different Downstream Electron Acceptors

Abstract: Plant-type ferredoxins in Arabidopsis transfer electrons from the photosystem I to multiple redox-driven enzymes involved in the assimilation of carbon, nitrogen, and sulfur. Leaf-type ferredoxins also modulate the switch between the linear and cyclic electron routes of the photosystems. Recently, two novel ferredoxin homologs with extra C-termini were identified in the Arabidopsis genome (AtFdC1, AT4G14890; AtFdC2, AT1G32550). FdC1 was considered as an alternative electron acceptor of PSI under extreme ferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…The 2Fe–2S iron–sulfur cluster binding proteins are necessary for photosynthetic electron transport in algae and Arabidopsis (Hanke et al ., 2004a; Hanke and Mulo, 2013; Guan et al ., 2018). The specific functions of different Fds in rice are not fully understood, however.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2Fe–2S iron–sulfur cluster binding proteins are necessary for photosynthetic electron transport in algae and Arabidopsis (Hanke et al ., 2004a; Hanke and Mulo, 2013; Guan et al ., 2018). The specific functions of different Fds in rice are not fully understood, however.…”
Section: Resultsmentioning
confidence: 99%
“…In photosynthetic tissues, AtFdC1 transports photosynthetic electrons from PSI to NiR and SiR in nitrogen and sulfur assimilation, respectively. In non‐photosynthetic tissues, the median redox potential of AtFdC1 may allow it to receive electrons from FNR (Guan et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process was measured via cytochrome c reduction (by Fd red ) under continuous illumination and a 14-fold decrease in the Michaelis constant K m was found vs the main Fd. FdC1 has a relatively high midpoint potential (-281 mV, ibid) and may not be primarily expressed in leaves [94], which would be in line with its poor reactivity with PSI. In a different approach, site-directed mutants of FdN studied with a low time resolution [95] showed that the effects of mutations are much smaller when looking at reduction by PSI than when looking at reduction of FNR by Fd red , concluding that Fd reduction by PSI is relatively robust toward amino-acid substitutions.…”
Section: Diffusion-limited Et Rates Between Fd and Its Partners Psi mentioning
confidence: 99%
“…In Arabidopsis, it was found that the minor ferredoxin FdC1 is unable to photoreduce NADP + via FNR, and this absence of activity was attributed to its high midpoint potential [93]. FdC1 can however interact with leaf-type electron acceptors including NiR, as with PSI, and can interact with FNR for reverse electron flow, albeit with a decreased efficiency [94]. The same authors showed that FdC1 might divert some reducing power away from FNR in Arabidopsis mutants overexpressing this Fd.…”
Section: Discrimination Of Fd2 Against Fnrmentioning
confidence: 99%